2013
DOI: 10.1186/1471-244x-13-173
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of structured patient-clinician communication with a solution focused approach (DIALOG+) in community treatment of patients with psychosis – a cluster randomised controlled trial

Abstract: BackgroundLarge numbers of patients with psychosis have regular meetings with key clinicians in the community. There is little evidence on how these meetings should be conducted to be therapeutically effective. DIALOG, a computer mediated procedure, was shown to improve outcomes in a European multi-centre trial. DIALOG structures the patient-clinician communication and makes it patient-centred, but does not guide clinicians as to how to respond to patients’ concerns. DIALOG has been further developed into DIAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 19 publications
(13 reference statements)
0
24
0
Order By: Relevance
“…A moderate or lower level of subjective quality of life is classified as a MANSA ≤ 60 points (Priebe et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…A moderate or lower level of subjective quality of life is classified as a MANSA ≤ 60 points (Priebe et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…This is a mixed-methods process evaluation nested within a cluster-randomised controlled trial that tested the effectiveness of DIALOG+ in the community treatment of patients with psychosis [ 6 , 13 ]. Guidelines for process evaluations were followed [ 12 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Detailed methodology of the trial design is reported in the protocol [ 13 ] and primary paper [ 6 ]. It was an exploratory, pragmatic, parallel group, cluster-randomised controlled trial.…”
Section: Methodsmentioning
confidence: 99%
“…The trial protocol is accessible in the public domain 56 [International Standard Randomised Controlled Trial Number (ISRCTN) 34757603]. This was a pragmatic, parallel-group, cluster randomised controlled trial.…”
Section: Trial Designmentioning
confidence: 99%